2007
DOI: 10.1175/jam2475.1
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of Single-Column Numerical Models for the Prediction of Radiation Fog

Abstract: The short-term forecasting of fog is a difficult issue that can have a large societal impact. Radiation fog appears in the surface boundary layer, and its evolution is driven by the interactions between the surface and lower layers of the atmosphere. Current NWP models poorly forecast the life cycle of fog, and improved NWP models are needed before improving the prediction of fog. Six numerical model simulations are compared for two cases from the Paris-Charles de Gaulle (Paris-CdG) fog field experiment. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 20 publications
0
71
0
7
Order By: Relevance
“…The boundary-layer 1D model COBEL has been coupled with another land-surface scheme: NOAH (Chen et al, 1997;Müller et al, 2005). A 1D model intercomparison for the forecasting of fog events (Bergot et al, 2006) showed that COBEL-ISBA and COBEL-NOAH behaved differently. This confirms the impact of the land-surface scheme on the forecast of low-visibility conditions.…”
Section: Simulations With No Mast: Nomastmentioning
confidence: 99%
“…The boundary-layer 1D model COBEL has been coupled with another land-surface scheme: NOAH (Chen et al, 1997;Müller et al, 2005). A 1D model intercomparison for the forecasting of fog events (Bergot et al, 2006) showed that COBEL-ISBA and COBEL-NOAH behaved differently. This confirms the impact of the land-surface scheme on the forecast of low-visibility conditions.…”
Section: Simulations With No Mast: Nomastmentioning
confidence: 99%
“…Many important features of fog have also been characterized using one-dimensional (1-D) modelling (Bergot et al, 2007;Tardif, 2007;Stolaki et al, 2015). However, to study some aspects of the characteristics of a fog layer, it has become necessary to explicitly simulate turbulent motion in 3-D as shown by Nakanishi (2000), who was the first to use a large eddy simulation (LES) for fog.…”
Section: Introductionmentioning
confidence: 99%
“…G. Waersted et al: Radiation in fog (Bergot et al, 2007;Steeneveld et al, 2015). Fog is difficult to model with numerical weather forecast models because of its local nature and the subtle balance between the physical processes that govern its life cycle, which must be parameterised in the models (Steeneveld et al, 2015).…”
mentioning
confidence: 99%